2014
DOI: 10.19026/rjaset.7.538
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plants and Equipment Management in Construction Industry of Iran

Abstract: During the recent years different people in charge have been considered about different costs of the plants in the construction industry. Usually it seems to be a big challenge for different people in charge and mainly contractors to decrease the costs of the projects through the optimum use of construction plants in order to increase the quality of the project and decrease time and cost. During the current study, researchers have been investigated about the construction plant use in the construction sites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The 3Rs idea has been identified as the most effective strategy among several that Malaysia has performed to decrease the waste volume in the construction industry. Reuse, recycle and reduce are the three key construction-related variables that have been considered in this approach [22]. Table 3 describes how each variable is implemented at the construction site in reducing the waste produced throughout the construction process.…”
Section: Environmental Initiatives Through the 3rs Conceptmentioning
confidence: 99%
“…The 3Rs idea has been identified as the most effective strategy among several that Malaysia has performed to decrease the waste volume in the construction industry. Reuse, recycle and reduce are the three key construction-related variables that have been considered in this approach [22]. Table 3 describes how each variable is implemented at the construction site in reducing the waste produced throughout the construction process.…”
Section: Environmental Initiatives Through the 3rs Conceptmentioning
confidence: 99%
“…Research conducted in China revealed that the principles of the 3Rs is a good way to protect the environment and stimulate the economy of a country. Aadal, et al [11], proposed the concept of 3R for the management of construction waste at the construction site. This study suggested that the construction industry needed a waste management to gain its benefits, especially for environmental and social problems.…”
Section: Introductionmentioning
confidence: 99%